Kabuki aktiermākslas un aktieru ārējā izskata semantika - Jerigina, Jana (Latvijas Universitāte, 2012)
Darba nosaukums -„Kabuki aktermākslas un aktieru ārēja izskata semantika”. Tēma ir aktuāla, jo Kabuki teātris ir viens no Japānas kultūras veidoliem. Japānas kultūrai ir cienītāji Latvijā, bet problēma ir Kabuki pieņemšana Latvijā . Darba mērķis ir pierādīt, ka Kabuki aktiermākslas un aktiera ārējā izskata neparastums ir šķērslis Kabuki tradīciju ieviešanai un popularizēšanai Latvijā. Pēc tēmas izpētīšanas tiek izdarīti secinājumi, ka Kabuki teātris ir unikāla parādība, kas līdz mūsdienām saglabā vēsturiskas tradīcijas. Pētījums sadalīts trijās daļās. Pirmā no tām ir veltīta vispārīgam Kabuki vēstures un aktieru apskatam, otrā daļā uzmanība tiek pievērsta aktiermākslas paņēmieniem, trešā – aktieru ārējam izskatam. Darba garums- 45 lapas.

The name of the work is „The semantics of Kabuki actor play and appearance”. This topic addresses the issue of understanding Kabuki theatre in Latvia. While Japanese culture is generally appreciated by Latvian population, Kabuki, an important aspect of Japanese culture, is often overlooked, deemed incomprehensible. The aim of the work is to prove that the peculiarity of Kabuki acting and appearance is what stands in the way of Kabuki acceptance and popularization in Latvia. This topic research allows for 2 conclusions: that the Kabuki theater is a unique phenomenon that has preserved historical traditions until nowadays;and that the changes in one part, for instance in acting, dictates the development of the actor's appearance, and vice versa. The research is divided to 3 parts. First of them is dedicated to Kabuki history and actor general review, in the second part attention is paid to the methods of the acting and in third - to Kabuki actors' appearances. The length of work is 45 pages.
The Semantics of Kabuki Actor Play and Appearance
Keywords: Āzijas studijas